SPRAWNE PAŃSTWO A CZŁONKOSTWO W PROCESIE INTEGRACJI EUROPEJSKIEJ Problem zmiany Konstytucji RP z 1997 r. w związku z członkostwem Polski w UE - Barcz, Jan (Wydział Prawa i Administracji UAM, 2006)
Accession to the European Union is for each state a substantial challenge of its political system. In order to satisfy its obligations arising from EU membership, and in particular in order to participate actively in the Community’s decision making process, the State must harmonise its system of government and its state system. This requirement is also true for Poland, even though the Polish Constitution of 1997 is a modern solution that establishes a solid and sound foundation for Poland’s participation in an international forum, and in the processes of European integration. And yet, already prior to Poland’s accession, it had been recognised that certain approximations of the Constitutional provisions would be needed. Today, two years after the accession, the postulated amendments of the Constitution are classified as those which are necessary (arising out of the State’s undertaking to transpose, or incorporate into the State’s legal system of the European Arrest Warrant), amendments that are very desirable (such as abolition of the requirement of a 50% participation of entitled voters in a referendum on the ratification of revision agreements amending the TEU, creation of grounds for the issue of executive orders, or of constitutional grounds for the electoral law compatible with the EU requirements) and the desirable (recommended) amendments (that would strengthen Parliament - government collaboration in matters related to the EU membership). However, the internal political situation in Poland has rendered implementation of those amendments impossible. If this situation continues, its consequences shall be not only infringement of the Community laws but also a much lower role that Poland will play in the Community’s decision making process in the future.
AN EFFICIENT STATE AND EU MEMBERSHIP IN THE INTEGRATION PROCESS Amendments in the Polish Constitution 1997 arising from Poland’s membership in the European Union